A PARP inhibitors in the treatment of breast cancer - A Review of literature - Jagoda Niewiadomska; Borys Bondos; Aleksandra Stępień; Alicja Paluch; Jakub Skrzypek; Aleksandra Niekra; Łukasz Fussek; Robert Kochan; Ewelina Wieczorek; Kacper Lee (Journal of Education, Health and Sport)
Introduction